Gen Z's Perception of the Interpersonal Communication Behavior of Guidance and Counseling Teachers That Can Build Rapport - Yuttami Keila Azahra; Moch Johan Pratama (Utan Kayu Publishing, 2026)
The research is based on the problem of negative perceptions of students who consider BK teachers as